Mối tương quan trong nội dung hoạt động giáo dục ngoài giờ lên lớp tại Trường Đại học Cần Thơ - Nguyễn, Thị Bích Phượng; Trần , Lương; Đặng , Thị Kim Liên (Tạp chí Giáo dục, 2022)
Apart from official school hours, universities need to organize a variety of extracurricular activities to help students develop soft skills during their university course. The article presents the current situation of educational extracurricular activities at Can Tho University. A survey of 520 managers/ lecturers and students at Can Tho University shows that the situation of implementation, the level of effectiveness and interest in the content of extra-curricular activities at Can Tho University is medium (mean =3,89). The correlation analysis between implementation, effectiveness and students’ interest in the content of extracurricular activities shows that there was a strong correlation between each of those factors. In addition, there we re differences in the assessment of managers, lecturers and students about the content of extracurricular activities. The research result is the basis for proposing measures to promote the implementation, students’ interest and eventually the effectiveness of the extracurricular activities for students of Can Tho University.